CULTURE AND INTERLANGUAGE STAGES EFFECT ON EFL STUDENTS’ POLITENESS IN REFUSALS - Widya . Wulandari; Berlin . Sibarani; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
ABSTRACTThe objectives of this study is to investigate the culture and interlanguage stages effect on EFL students’ politeness in refusals. This study was a qualitative research. The data were taken from refusal expressions made by EFL Malay and Batak Junior high school students with initial stage (stage 1 interlanguage) and free variation stage (stage 2 interlanguage). The data of this study were collected by using elicitation techniques by using Discourse Completion Task (DCT), pictures and Interview. The number of the subjects involved in this study was taken by using snowball technique and the total number were twelve subjects. The results of this study showed that both culture and interlanguage stages affect the EFL students’ politeness in refusals. In Bataknese EFL students, the realization of politeness in refusal tends to be more affected by the culture rather than the interlanguage stages. While in Malay, culture and interlanguage stages have the same effect in the realization of politeness in refusals.Keywords: Culture, Effect, Interlanguage Stages,  Politeness, Refusals